Super Resolution Imaging Based on a Dynamic Single Pixel Camera - Yao Zhao; Qian Chen; Xiubao Sui; Hang Gao (IEEE Photonics Journal)
In this paper, we present a super resolution imaging method based on a dynamic single pixel camera. First, the proposed method obtains subhigh-resolution (HR) images with subpixel shifts by the dynamic single pixel camera. To achieve this purpose, the patterns on the digital micromirror device are subpixel shifted instead of mechanical scanning. Then, the final HR image can be reconstructed by sub-HR images and wiener filter. In order to avoid the subpixel shifts error that caused by the instability of the system, a subpixel registration algorithm is adopted. Besides, to improve the signal-noise-ratio (SNR) performance of the measurements, a simple and effective method based on the correlation of the signal and the randomness of the noise is adopted. Compared with traditional single pixel imaging system, the proposed method has a remarkable performance at spatial resolution and SNR. The feasibility of the proposed method is demonstrated by simulations and experiments.